2018
DOI: 10.1016/j.ccell.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Microbiota in Colorectal Cancer

Abstract: Experimental evidence from the past years highlights a key role for the intestinal microbiota in inflammatory and malignant gastrointestinal diseases. Diet exhibits a strong impact on microbial composition and provides risk for developing colorectal carcinoma (CRC). Large metagenomic studies in human CRC associated microbiome signatures with the colorectal adenoma-carcinoma sequence, suggesting a fundamental role of the intestinal microbiota in the evolution of gastrointestinal malignancy. Basic science establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
436
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 577 publications
(497 citation statements)
references
References 120 publications
11
436
0
9
Order By: Relevance
“…UC has a complex, multifactorial etiopathogenesis, including host genetic, environmental and microbial factors, which has not been fully elucidated. Recent in‐depth studies have found that gut microbiota—as a complex ecosystem—are associated with many diseases . Intestinal mucosal homeostasis is based on the physiological coexistence of an abundant and diverse commensal bacterial ecosystem that colonizes the intestine .…”
Section: Introductionmentioning
confidence: 99%
“…UC has a complex, multifactorial etiopathogenesis, including host genetic, environmental and microbial factors, which has not been fully elucidated. Recent in‐depth studies have found that gut microbiota—as a complex ecosystem—are associated with many diseases . Intestinal mucosal homeostasis is based on the physiological coexistence of an abundant and diverse commensal bacterial ecosystem that colonizes the intestine .…”
Section: Introductionmentioning
confidence: 99%
“…CRC development and outcome are thus largely influenced by the immune response and its microenvironment. In addition, a large amount of microorganisms are also present in this colonic tumor microenvironment and could play a role in carcinogenesis …”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer patients often exhibit a distinct microbiota composition (dysbiosis) compared to that of a healthy population . Recently, Wong et al .…”
Section: Introductionmentioning
confidence: 99%
“…Large metagenomic studies in human CRC linked certain microbiome signatures with the colorectal adenoma‐carcinoma sequence. Although dominant species in CRC carcinogenesis remain poorly defined, an important role of Fusobacterium nucleatum ( Fn ), Escherichia coli , and Bacteroides fragilis coming from experimental evidence is emerging . A striking example is our recent identification of the link between Fusobacterium nucleatum and the chemoresistance to CRC .…”
Section: Introductionmentioning
confidence: 99%